2016
DOI: 10.1002/ece3.2588
|View full text |Cite
|
Sign up to set email alerts
|

Using multiple traits to assess the potential of introduced and native vines to proliferate in a tropical region

Abstract: Predicting the invasive potential of introduced species remains an ongoing challenge due to the multiple interacting regional and global processes that facilitate the introduction and proliferation of alien species. This may be particularly true in regions where native species are increasingly reported as expanding and impacting ecosystems in ways indistinguishable from alien ones. Current approaches to assess the invasive potential of plants may be limited by the choice of traits used and the exclusion of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…An increasing number of studies have shown that tropical forests are experiencing remarkable changes in structure and dynamics (Phillips and Gentry 1994, Condit 1998, Allen et al 2010, Enquist and Enquist 2011, which includes an outstanding proliferation of lianas in the Neotropics (Phillips et al 2002, Schnitzer and Bongers 2011, Delgado et al 2016, Hogan et al 2017. Determining whether these changes are also present in earlier ontogenetic stages and linked to abiotic and biotic factors is a central goal in ecology and conservation biology.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown that tropical forests are experiencing remarkable changes in structure and dynamics (Phillips and Gentry 1994, Condit 1998, Allen et al 2010, Enquist and Enquist 2011, which includes an outstanding proliferation of lianas in the Neotropics (Phillips et al 2002, Schnitzer and Bongers 2011, Delgado et al 2016, Hogan et al 2017. Determining whether these changes are also present in earlier ontogenetic stages and linked to abiotic and biotic factors is a central goal in ecology and conservation biology.…”
Section: Discussionmentioning
confidence: 99%
“…In these post-agricultural landscapes native and non-native vines blanket crops, second-growth vegetation, and forest edges ([42, 44], e.g., [66]). The intentional introduction of non-native vines, repeated sowing of vine seeds, and soil disturbance [47] could have favored the spread of a small group of vines in areas that were formerly devoted to agriculture. Thus vector-vine interactions may explain discrepancies between our observations and those made by others.…”
Section: Discussionmentioning
confidence: 99%
“…In Puerto Rico vines form compact communities—hereafter vine patches–that cover ~3% (49.5 km 2 ) of our study area [44]. The increasing proliferation of vines most likely is the result of the decline of an otherwise thriving agricultural economy [46] and the repeated introduction of numerous alien vine species with agricultural value [47].…”
Section: Methodsmentioning
confidence: 99%